The VTA Agreement: How Has it Done? - Sedano, Richard (Maine Policy Review, 1993)
The dramatic changes in telecommunications in the past decade have caused many states to try new approaches to the regulation of local telephone companies. The "Vermont Telecommunications Agreement" was one of the earliest attempts at such innovative regulatory approaches. To learn more about that experience, the PURE ’93 conference and Maine Policy Review invited representatives with three different perspectives on the Vermont experience to share their observations.